Business intelligence (BI) in logistics - Gyenge, Balázs; Mészáros, Kornélia; Tari, Katalin (Studia Mundi – Economica, 2019)
Rapidly developing logistics and supply chain/net logistics and its material and information flow are not any more limited to the basic functions of logistics (WTS – warehouse, transport, storage services) or its typical cost and time decreasing aims seemingly has begun to change in the supply chain. More and more goals and added service pop up on behalf of the rising of the customer service level. According to the developed economies logistics aren’t just a service any more for a long time, it is more like a profit centre or more than that it is became to turn a real strategic field. It can be feel that logistics issues have a greater influence to basic decisions like “what to produce, where to produce, where to store, how big volume we need, who should be chosen for logistics intermediaries, and so on” These issues are natural part of the strategic management. In the past few decades, these changings are not just focus alteration from marketing supremacy but natural good sense of that we should keep systems in holistic way of thinking and now we don’t searching optimum points locally. Rapid changing of technologies in material and information flow makes a more complex view possible and gives different objectives in applications. Quickly changing customer needs, market circumstance, customised ordering habits, as well as lot of hidden information, so vast which needs entirely new methods to process. Traditional methods and applications don’t give satisfying information to make various decisions. That’s why traditional business information systems and communication channels we need to equip with a series of artificial intelligent tools to reach new levels of customer service, intelligent automatization, new flexibilities for our customers and management strategy. In this paper we will make an attempt to explore possibilities of business intelligence especially the advantages of the BI applications and methods.